Narrativas ao Sul: viagem e música em quatro romances de Assis Brasil - André Tessaro Pelinser; Maria Zilda Ferreira Cury (Estudos de Literatura Brasileira Contemporânea)
Visitantes ao Sul is the title of a set of novels written by Luis Antonio de Assis Brasil and published from 2001 to 2012. In such novels, the writer deals with traveling as a literary theme, presenting characters in constant movement and, sometimes, in situations of displacement. This paper aims at analysing not only the transit experienced by the four protagonists o f the novels, taking into account their contacts with diverse cultural spaces, but also intends to reflect upon their insertion in the specific temporality of modernity and in the so - called fin de siècle . This paper also discusses one feature that characte rises that set of novels: music, which frequently provides the characters’ mobility with a rhythm, implying the development of a comprehensive metaphor and suggesting new meanings to those narratives.